‘New’ and ‘old’ wars – the changing dimensions of warfare - Antczak, Anna (Przegląd Politologiczny, 2018)
The article aims to present the issue of ‘old’ versus ‘new’ wars in relation to their specific features. It focuses on the characteristics of both phenomena, as well as providing an analysis of the causes and sources of armed conflicts and their changing dimensions. Methods of waging war have changed along with the political, economic, social and technological developments which have been observed over the years. The very philosophy of war has undergone changes in a similar way. The article aims to identify the direction of changes in the dimensions of war. It also provides an insight into the privatization of warfare and the constantly growing importance of non-state actors in shaping the international order, and therefore their role in post-modern wars.